INDUSTRI HALAL: MENGEMBANGKAN HASRAT DAN LOGIKA KONSUMSI - Saepul Bahri; Deden Hidayat; Agus Nurcholis Saleh (Universitas Mathla’ul Anwar Banten, 2021)
This paper is actually the author's desire to contribute to the idea of ​​halal thought initiated by most of the world's Muslims, the author does not interpret halal simply and narrowly but the author tries to interpret halal by changing the paradigm of Muslims that halal must be expanded into a halal industry. in this world. This paper inspires especially Muslims in Indonesia to have the courage to create new halal industries, developed in various aspects of the needs of the wider community. In this paper the author shows how great the potential of the halal industry is, but it must be driven by politics and productive market mechanisms. According to the author's research, the halal industry is actually a religious commandment, namely Islam, but more importantly the substance of the halal industry is to develop the desire and logic of consumption, why because the halal industry will progress and develop depending on the consumer who consumes goods, if the desire and logic of consumption is weak , then as good and as productive as any halal industry will not develop and experience progress, therefore the desire and logic of consumption is very important to be understood by Muslim entrepreneurs who will develop the halal industry.